Associations of circulating insulin-like growth factor-I with intake of dietary proteins and other macronutrients - Watling, C; Kelly, R; Tong, Y; Piernas, C; Watts, E; Tin Tin, S; Knuppel, A; Schmidt, J; Wrightson, R; Key, T; Travis, R (Elsevier, 2021)
Background: Circulating insulin-like growth factor-I (IGF-I) is associated with the risk of several cancers. Dietary protein intake, particularly dairy protein, may increase circulating IGF-I; however, associations with different protein sources, other macronutrients, and fibre are inconclusive.